Unraveling the Fast Fashion Dilemma: An Analysis of the Role of Knowledge, Responsibility, Values, and Concern in Shaping Green Consumer Behavior - Apriliyanto, Nanang; Nugroho, Mahfud; Rigiuma, Aldistri nadia (Amkop Management Accounting Review (AMAR), 2025)
The fast fashion business has the potential to engage in greenwasting practices, as it is estimated to contribute 92 million tons of waste annually. Although this business is growing significantly both in Indonesia and globally, it has created a significant challenge for global stakeholders, including the Indonesian government, to address the amount of waste generated by fast fashion. This study aims to analyze the factors influencing Green Consumer Behavior in the context of fast fashion trends. The study in this research is a causal-based quantitative approach to the Green Consumer Behavior scheme. Primary data comes from an online questionnaire. The population in this study was 200 respondents who exhibit impulsive behavior towards fashion products, but they also care about the environment. For data analysis, the tool used was Smart-PLS, a tool with SEM. Consumer Environmental Responsibility, Perceived Value, Environmental Knowledge, and Environmental Concern have a positive and significant effect on Green Consumer Behavior. Consumer Environmental Responsibility also shows a positive and significant relationship with Perceived Value and Environmental Concern, while Environmental Knowledge has no significant effect on Environmental Concern. Environmental Concern mediates the influence of Consumer Environmental Responsibility and Perceived Value on Green Consumer Behavior but not Environmental Knowledge.